Vibrational ground state energy for confined molecules - Filho, Elso Drigo [UNESP]; Silva, Josimar Fernando Da [UNESP] (IOP Publishing, 2019)
The ground state vibrational energies for three confined diatomic molecules (nitrogen, lithium and NaH) are determined by using the variational method. The approach proposed allows us to build trial eigenfunctions based on wave functions obtained from the supersymmetric quantum mechanics formalism. The Morse potential is used to simulate the molecular bound and the confinement is analyzed by introducing two barriers with the minimum of the potential inside this region. The methodology adopted was successfully used previously to describe the hydrogen molecule. The conclusion from these results is that the approach can be extended for other diatomic molecules.